2014
DOI: 10.1186/1471-2407-14-190
|View full text |Cite
|
Sign up to set email alerts
|

Epidermal growth factor receptor gene polymorphisms are associated with prognostic features of breast cancer

Abstract: BackgroundThe epidermal growth factor receptor (EGFR) is differently expressed in breast cancer, and its presence may favor cancer progression. We hypothesized that two EGFR functional polymorphisms, a (CA)n repeat in intron 1, and a single nucleotide polymorphism, R497K, may affect EGFR expression and breast cancer clinical profile.MethodsThe study population consisted of 508 Brazilian women with unilateral breast cancer, and no distant metastases. Patients were genotyped for the (CA)n and R497K polymorphisms… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
18
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(19 citation statements)
references
References 41 publications
(42 reference statements)
0
18
1
Order By: Relevance
“…The TME stimulus was induced by simultaneous exposure of luminal-A breast tumor cells to representatives of 3 relevant arms of the TME: 1) estrogen, the key hormonal factor in luminal-A tumors, which by definition, all express ER [18,19]; 2) TNF-a, a representative of the inflammatory arm; this cytokine has direct tumor-promoting effects in breast cancer and is expressed by ;90% of breast cancer patients with recurrent disease, including ER+ breast tumors [39][40][41][42][43]; and 3) EGF, a growth-stimulating factor that prevails in breast tumors [44,45]. Luminal-A tumors express EGFR and are characterized by high levels of ErbB3 [46][47][48]. EGF was shown to act through EGFR-ErbB3 dimers in luminal-A breast tumor cells [46] and to induce signaling in such cells through indirect activation of ER [48][49][50][51][52].…”
Section: Introductionmentioning
confidence: 99%
“…The TME stimulus was induced by simultaneous exposure of luminal-A breast tumor cells to representatives of 3 relevant arms of the TME: 1) estrogen, the key hormonal factor in luminal-A tumors, which by definition, all express ER [18,19]; 2) TNF-a, a representative of the inflammatory arm; this cytokine has direct tumor-promoting effects in breast cancer and is expressed by ;90% of breast cancer patients with recurrent disease, including ER+ breast tumors [39][40][41][42][43]; and 3) EGF, a growth-stimulating factor that prevails in breast tumors [44,45]. Luminal-A tumors express EGFR and are characterized by high levels of ErbB3 [46][47][48]. EGF was shown to act through EGFR-ErbB3 dimers in luminal-A breast tumor cells [46] and to induce signaling in such cells through indirect activation of ER [48][49][50][51][52].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, EGFR genetic polymorphisms have shown a predictive value for the risk of breast cancer [16]. A previous case-control study revealed that cases with a polymorphism at nucleotide 2607 in EGFR exon 20 (G2607A; Q787Q; rs 10251977) are more susceptible to lung cancer [17].…”
Section: Introductionmentioning
confidence: 99%
“…41 in our series was treated in second line with Cetuximab with partial response (8). In other tumor systems, the integrated assessment of egfr polymorphisms, histopathological features and staging factors were shown to contribute to prognostic estimates in breast cancer (27). Our pilot study data indicated that egfr short CA-SSR-1 sequences were significantly associated with the more aggressive B2/B3, B3 and B3/C WHO histotype groups (28) Furthermore, egfr-FISH positivity was associated with malignant behaviour in thymomas in 5 out of the 7 cases with available FU.…”
Section: Discussionmentioning
confidence: 75%